Rediscovered after 77 years: Odontodiaptomus thomseni - a rare species of calanoid (Crustacea: Copepoda) from South America - Perbiche-Neves, Gilmar; Boxshall, Geoff A.; Rocha, Carlos E. F. da; Nogueira, Marcos G. [UNESP] (Sociedade Brasileira de Zoologia, 2012)
The freshwater copepod Odontodiaptomus thomseni (Brehm, 1933) (Calanoida: Diaptomidae) is a rare species that has been reported only once - in its original description (BREHM 1933). The lack of subsequent records led to its inclusion in the Red List of threatened species (IUCN). Here we present a new record for O.thomseni. It was discovered in Salto Grande reservoir, which is located in the lower stretches of the Uruguay River, between Uruguay and Argentina, at the River Plate basin. In January 2010, three specimens (two males and one female) were found, and these were studied in detail using scanning electron microscopy (SEM). We only had material of Odontodiaptomus paulistanus (Wright, 1936) for comparison, but the position of the lateral spine in right P5 of the male, and the shape and size of lateral wings of the female are especially distinctive. Odontodiaptomus thomseni remains a rare species and we recommend keeping it on the IUCN Red List.
Keywords: Copepod; rare; red list; taxonomy